The chemistry of cross-linked polymeric vesicles and their functionalization towards biocatalytic nanoreactors - Moreno, Silvia; Voit, Brigitte; Gaitzsch, Jens (Colloid and Polymer Science, 2021)
Self-assembly of amphiphilic block copolymers into polymersomes continues to be a hot topic in modern research on biomimetics. Their well-known and valued mechanical strength can be increased even further if they are cross-linked. These additional bonds prevent a collapse or disassembly of the polymersomes and open the way towards smart nanoreactors. A variety of chemistries have been applied to obtain the desired cross-linked polymersomes, and therefore, the chemical approaches performed over time will be highlighted in this mini-review. Due to the large number of studies, a selected set of photo-cross-linked and pH-sensitive polymersomes will be specifically highlighted. This system has proven to be a very potent candidate for the formation of nanoreactors and drug delivery systems, and even for the formation of functional multicompartment cell mimics. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-04-14
Keywords: Cross-linking; Nanoreactors; Polymersomes; Vesicles